Natural Hierarchically Structured Highly Porous Tomato Peel Based Tribo‐ and Piezo‐Electric Nanogenerator for Efficient Energy Harvesting. (13th May 2021) - Saqib, Qazi Muhammad; Khan, Muhammad Umair; Song, Hyunjae; Chougale, Mahesh Y.; Shaukat, Rayyan Ali; Kim, Jungmin; Bae, Jinho; Choi, Min Joo; Kim, Seong Chan; Kwon, Ohbin; Bermak, Amine
Abstract: To mitigate future global energy challenges, it is vital to utilize natural resources to harness sustainable and environmentally‐friendly energy. This paper explores the tribo‐ and piezo‐electric functionalities of tomato peel (TP) to fabricate a nature‐driven hybrid nanogenerator. Tomato is one of the most cultivated vegetables globally, however, a significant amount of TP is disposed after utilization in the food processing industries. The TP possesses a natural hierarchically placed highly porous structure, which is helpful to enhance the output performance of both piezo‐ and tribo‐electric devices. This work shows that a TP based piezo‐electric nanogenerator can produce an open circuit voltage of 24.5 V, short circuit current of 2.5 µA, and maximum instantaneous power of 19.5 µW. In addition, the TP based tribo‐electric nanogenerator generates open circuit voltage, short circuit current, and instantaneous power of 135 V, 81 µA, and 3750 µW, respectively. Combining two NGs functionalities, the proposed TP based tribo‐ and piezo‐electric nanogenerator (TP‐TPENG) shows enhanced output performance with the rectified open circuit voltage, short circuit current, and maximum instantaneous power of 150 V, 84 µA, and 5400 µW, respectively. These results show that the TP‐TPENG can offer a new pathway toward bio‐based nanogeneration and self‐powered sensing green technologies. Abstract : This paper reports tribo‐ and piezo‐electric functionalities of tomato peel (TP) to fabricate TP‐based tribo‐ and piezo‐electric nanogenerators (TP‐TPENGs). TP possesses a natural hierarchically placed highly porous structure, which is helpful to enhance the output performance of piezo‐ and tribo‐electric devices. The maximum power of TP‐TPENG reaches 5400 µW. This work offers huge potential toward bio‐based nanogeneration for green technologies.